The Pathway to Sustainable Loyalty: Connecting Environmental Commitment, Experience, and Revisit Intentions - Muhammad Asim Nawaz; Ahsan Zubair; Muhammad Rizwan Arshad (Social Science Review Archives, 2025)
This study is focused on deepening the understanding of tourist destination loyalty in the context of ecotourism. The study estimates the vital relationship between environment commitment, Eco destination experience and destination loyalty. The study considered five independent perspectives contributing in enhancing the experience of the tourist at destination. Moreover, the authors have developed a questionnaire-based survey to collect the data from experienced tourists having prior exposure of the ecotourism. The data was collected from the urban centers of the Pakistan mostly the provincial and national capital. 418 correct and complete responses were used for data analysis. The authors have used the Smart PLS-SEM analysis to estimate the relationship between the variables and quality of the data. The measurement model is used to check the reliability of data and structural model explains the internal relationships of variables. Further, the study results show that all the three variables have positive relationship with each other and make stronger contribution to enhance the impact of destination loyalty in ensuring the success of business model. In the end, the study presents the theoretical and practical contribution.